2D Euler equation on the strip: Stability of a rectangular patch. Issue 1 (2nd January 2017) - Beichman, Jennifer; Denisov, Sergey
ABSTRACT: We consider the 2D Euler equation of incompressible fluids on a strip ℝ× 𝕋 and prove the stability of the rectangular stationary state χ | x |< L for large enough L .